Pengaruh Aktivator dan Laju Alir dengan Metode Slow Sand Filter Menggunakan Kombinasi Karbon Aktif Alami untuk Pengolahan Air Telaga - Pratiwi, Safitri Wahyu; Amalia, Aussie (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Lake water contaminated with domestic sewage is a serious problem as it can pollute the surrounding environment, as in Telaga Rambit, Gresik. Turbid water quality indicates pollution, so a treatment process is needed before use. This study aims to analyse the effect of activator type and flow rate on the filtration process using the slow sand filter (SSF) method, with a combination of coconut shell charcoal and rice husk charcoal media. The flow rate variations used were 0.1 m³/h and 0.3 m³/h, with hydrochloric acid (HCl) and phosphoric acid (H₃PO₄) activators. The results showed that Reactor B, using H₃PO₄ at a flow rate of 0.1 m³/h, was the most effective variation in reducing pollutant levels, namely BOD by 1.9 mg/l, COD by 6.26 mg/l and TSS by 12 mg/l at the 25th sampling time. The H₃PO₄ activator has been shown to increase the adsorption capacity of activated carbon media, particularly in the capture of suspended solids. The low flow rate also provided better stability during the filtration process, allowing for more effective particle retention. After 25 minutes, the filtration media had not reached saturation point, indicating that filtration could be improved with longer contact times.